Optimization of Heritage Tourism Village Marketing Through the Pentahelix Model (Case Study of Terban Village) - Denada Grehastuti; Supriyono Supriyono; Sutono Sutono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the marketing strategy of Terban Tourism Village in Kudus Regency using the Pentahelix model approach. The research employs a descriptive qualitative method with data collection techniques including documentation, in-depth interviews, surveys, and observations. Data analysis uses the Miles et al. model, comprising data condensation, data presentation, and conclusion drawing. The results show that Terban Tourism Village has potential as a heritage tourism destination with advantages in the Patiayam Archaeological Site, Grenjengan Waterfall, and Japanese Cave, but collaboration among Pentahelix stakeholders is not yet optimal. Analysis of the tourism marketing mix identifies strengths in unique tourist attractions and multi-channel marketing strategies, while weaknesses are found in amenities, heritage value interpretation, and minimal academic involvement. SWOT analysis places Terban Tourism Village in Quadrant I (X=0.89; Y=1.02), indicating a strategic position for implementing aggressive growth strategies. Key recommendations include developing integrated heritage tourism products, optimizing digital marketing, strengthening interpretation through collaboration with academics, revitalizing the Tourism Awareness Group (Pokdarwis), and establishing a Pentahelix coordination forum. Strategy implementation requires a clear role distribution among the five Pentahelix actors to realize Terban Tourism Village as a leading sustainable heritage tourism destination.